Comprehensive Analysis of RUNX and TGF-β Mediated Regulation of Immune Cell Infiltration in Breast Cancer - Gao, Liang; Zhou, Fangfang (Frontiers in Cell and Developmental Biology, 2021)
RUNX transcription factors can serve as both transcription activators and repressors during biological development, including immune cell maturation. RUNX factors have both tumor-promoting and tumor-suppressive roles in carcinogenesis. Immune cell infiltration and the tumor immune microenvironment have been found to be key regulators in breast cancer progression, treatment response, and patient outcome. However, the relationship between the RUNX family and immune cell infiltration in breast cancer remains unclear. We performed a comprehensive analysis to reveal the role of RUNX factors in breast cancer. Analysis of patient data in the Oncomine database showed that the transcriptional levels of RUNX proteins in breast cancer were elevated. KM plotter analysis showed that breast cancer patients with higher expression of RUNX proteins had better survival outcomes. Through analysis of the UALCAN database, we found that the transcriptional levels of RUNX factors were significantly correlated with some breast cancer patient characteristics. cBioPortal analysis showed the proportions of different RUNX genomic alterations in various subclasses of breast cancer. We also performed gene ontology and pathway analyses for the significantly differentially expressed genes that were correlated with RUNX factors in breast cancer. TIMER database analysis showed that immune cell infiltration in breast cancer could be affected by the transcriptional level, mutation, and gene copy number of RUNX proteins. Using the GSCA database, we analyzed the effects of RUNX gene methylation on the level of immune cell infiltration in breast cancer. We found that the methylation level changes of RUNX2 and RUNX3 had opposite effects on immune cell infiltration in breast cancer. We also analyzed the relationship between the methylation level of RUNX genes and the TGF-β signaling pathway using the TISIDB database. The results showed that the methylation levels of RUNX1 and RUNX3 were correlated with the expression of TGF-β1. In summary, our analysis found that the RUNX family members can influence the infiltration of various immune cells in breast cancer depending on their expression level, mutation, gene copy number, and methylation. The RUNX family is an important regulator of immune cell infiltration in breast cancer and may serve as a potential prognostic biomarker.